(untitled) (Journal of Nuclear Technology in Applied Science, 2019)
Background: The skin is considered to be a radiosensitive organ. Low-level laser therapy (LLLT) known as photobiomodulation is a growing technology used to treat multitude of conditions that require stimulation of the healing process. Aim of the work: The present work was conducted to study the possible biostimulatory effects of LLLT on the skin of gamma irradiated mice. Materials and methods: 264female mice were used in the present experiments were divided into 6 groups: Group (1): Non irradiated control group. Group (2): Laser irradiated group. Group (3.1): One shot gamma irradiated group. Group (3.2): One shot + laser irradiated group. Group (4.1): Cumulative gamma irradiated group. Group (4.2): Cumulative + laser irradiated group. Exposure of the animals to gamma rays was performed using a cesium-137 source. Two modes of exposure were used, a shot modality where the mice were irradiated with a single sub lethal dose of 5 Gy. While in the other mode, the same dose was given in fractionated daily installations of 1 Gy. Treatment of mice with laser was carried out using a computerized scanner emitting He-Ne (CW) at a wavelength of 632.8 nm. The fluence was 5J/cm2. Histopathological (HP) assessment of skin biopsies derived from the experimental mice was done immediately after each sacrification.Conclusion: LLL therapy accelerates skin regeneration post exposure to ionizing radiation in both shot and cumulative mode. Our conclusions also highlight the biostimulatory effect of He-Ne LLL on hair follicles.